Formulation of Drying and Non Drying Oil Alkyd Resin from Palm Oil (Elaesis guineensis jacq.) and Tuna Fish Oil (Thunnus sp.) toward Acid Number Value and Non Volatile Content as Surface Coating Resin - Indrawaty, Desmilia Sefti; Amalia, Rizka (Vocational College of Universitas Diponegoro, 2022)
Resin is a polymer chemical substance that is made up of monomers from carbon and nitrogen. Alkyd resin, a surface coating resin, produced by polycondensation reaction between polybasic and polyhydric alcohols, modified with monobasic acids or their anhydrides, and drying oil at controlled temperatures. Alkyd resin is widely used in the paint and surface coating industries. The advantages of this resin are its strong chemical and thermal resistance, quick drying power, and inexpensive cost. Alkyd resins can be produced from natural oil (palm and tuna fish oil). Oil derived from palm and tuna fish is known as natural oil. Tuna fish oil includes 40.04 % oleic acid. The oleic content is suitable for use in the alcoholysis process in the production of alkyd resins. The major ingredients in this study were tuna fish oil and palm oil. The aim of this research is to determine the influence of a combination of palm oil:tuna fish oil ratio, amount of pthalic anhydride, and temperature of alcoholysis process on the value of acid number and non-volatile content of alkyd resin was investigated using a Completely Randomized Design (CRD).